The Importance of Store Image and Retail Service Quality in Private Brand Image-Building - Adi Alić; Emir Agić; Merima Činjarević (Entrepreneurial Business and Economics Review)
Objective: The purpose of this research is to highlight the role which store image and retail service quality can play in private brand image-building in the context of an emerging market in South-Eastern Europe (i.e. Bosnia and Herzegovina). We propose to address this issue by seeking answers to the following questions: (1) Does a ‘halo effect’ take place between the store image and the private brand image? (2) How does consumer’s evaluation of the quality of the service delivered by a retailer affect the image of its private brand?